ANALISIS PERSEPSI MAHASISWATERHADAP PENGUNAAN GOOGLE CLASSROOM METODE SEBAGAI MEDIA PEMBELAJARAN MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCED ANALYSIS (IPA) - Muhammad Alfarisi (JINTECH: Journal Of Information Technology, 2021)
Google Classroom is one of the learning media used by Information Technology Education students in carrying out the teaching and learning process that makes it very easy for users. Service quality in Google Classroom is carried out using the Webqual 4.0 method and Importance Performance Analysis which focuses on four assessment criteria, namely Usability, Information Quality, Service (Interaction) and Overall (Overall), as well as calculating the quality value and expectations of the service. Google Classroom app. The method used in this research is descriptive quantitative. Data collection techniques were carried out by distributing questionnaires or questionnaires to a sample of 100 respondents. The Google Classrom application as a whole is good. From the results of the calculation of the gap (GAP) the quality of Google Classroom shows that the GAP is negative, namely -0.04 meaning that the user feels that the performance of Google Classroom has not met what the user wants, then the results of the analysis based on the IPA quadrant obtained 2 indicators in Quadrant A, 8 indicators in Quadrant B, 7 indicators in Quadrant C, and 5 indicators in Quadrant D